(3WQGR GdMdI hTaGA GdZdI aj TQM MdI GdSjQi aj eOM NjQ GdhQis - (3CMeO Hf jhSa Hf eGdc GdQYjfj GdZQfGWj GdCfOdSj, CHh LYaQ , J (B779 (3g` s; (3GHf LGHQ , eMeO Hf CMeO Hf Ydj Hf LGHQ GdCfOdSj GdghGQj, TeS GdOjf CHh YHO Gddg,J (B780 (3g` s ((3eMeO Hf EHQGgje Hf SGde GdQhei s)
(3ChdgG (B:s
(3GdMeO ddg GdHOjY GdCaYGd , GdJhbjY Yf GdCeKGd CeG HYO aEfg deG cGfJ GdbUjOI GdefXheI ai Yde GdHOjY GdJi CfTCgG UGMHfG GdEeGe GdYdGeI TeS GdOjf CHh YHO Gddg eMeO Hf LGHQ GdCfOdSi QCjJ Cf CVY dgG TQMkG jLdh YQGFS eYGfjgG s
(3BNQgG (B:s
(3bdJ gfG GfJgi GdcdGe Ydi gPg GdbUjOi GdJi gi Cced GdbUGFO Udi Gddg Ydjg hYdi Bdg hCUMGHg GdPjf SHbJ dge GdYGOI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdHdGZIs